Analisis Pengaruh Brand Awareness, Perceived Quality, dan Customer Experience terhadap Repurchase Intention dengan Brand Equity sebagai Variabel Mediasi: Studi pada Merek Miniso di Kota Semarang - Muhammad Fauzi; Imroatul Khasanah (Faculty of Economics and Business Diponegoro University, 2026)
This study aims to analyse the effect of perceived quality, brand awareness, and customer experience on repurchase intention, with brand equity and customer satisfaction as mediating variables. The research was conducted on Miniso consumers in Semarang using a quantitative approach. Data were collected from 160 respondents through a structured questionnaire and analysed using Structural Equation Modelling-Partial Least Squares (SEM-PLS). The results show that perceived quality, brand awareness, and customer experience have a positive and significant effect on brand equity. Furthermore, brand equity significantly affects customer satisfaction and repurchase intention, while customer satisfaction also has a significant effect on repurchase intention. In addition, brand equity and customer satisfaction have been shown to mediate the relationship between the independent variables and repurchase intention. The model explains 54.5% of the variance in repurchase intention. These findings highlight the importance of strengthening brand equity and enhancing customer satisfaction to improve consumer repurchase intention in the lifestyle retail industry.